DIVERSIFICATION OF FINANCING AS AN EFFORT TO INCREASE PROFITABILITY AT ISLAMIC COMMERCIAL BANKS IN INDONESIA - Widia Ayu Lestari (IQTISHADUNA, 2020)
This study aims to see the picture and the effect of diversification of bank financing on profitability in Islamic Commercial Banks in Indonesia for the period 2013-2018. ROA profitability during the last six years has fluctuated and tends to decline. This is due to the high level of problem financing. The research method used in this research is the causality method with a quantitative approach. The population in this study is Sharia Commercial Banks in Indonesia. The method used for sampling in this research is purposive sampling with a total sample of ten BUS in Indonesia for 6 years of research. The data used is secondary data. The statistical analysis technique used in this study is panel data regression analysis using Eviews 9. The dependent variable in this study is profitability with ROA ratios and independent variables in this study are diversification of contract type financing, financing diversification of types of use, and diversification of economic sector financing. The level of diversification in this study uses the Hirchman Herfindalh Index (HHI) formula. The results showed that the Diversification of Financing Contract Type had a negative effect on profitability, the Diversification of Financing Type of Use influenced the profitability of ROA with a positive direction and the Diversification of Financing the Economic sector had a positive effect on profitability.